2013
DOI: 10.1262/jrd.2012-144
|View full text |Cite
|
Sign up to set email alerts
|

Targeted DNA Methylation Analysis by High Throughput Sequencing in Porcine Peri-attachment Embryos

Abstract: The purpose of this experiment was to implement and evaluate the effectiveness of a next-generation sequencing-based method for DNA methylation analysis in porcine embryonic samples. Fourteen discrete genomic regions were amplified by PCR using bisulfite-converted genomic DNA derived from day 14 in vivo-derived (IVV) and parthenogenetic (PA) porcine embryos as template DNA. Resulting PCR products were subjected to high-throughput sequencing using the Illumina Genome Analyzer IIx platform. The average depth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…NGS generates thousands of read sequences for each sample, unlike traditional bisulfite sequencing with only 10–20 sequences. The greater the read number, the higher the statistical power of analysis for detecting even subtle differences in methylation between samples [33]. ChIP data are represented as the mean ± SD of 6 different treatments (n=6) and analyzed by two-tailed paired t-test with significance level P < 0.05 as above.…”
Section: Methodsmentioning
confidence: 99%
“…NGS generates thousands of read sequences for each sample, unlike traditional bisulfite sequencing with only 10–20 sequences. The greater the read number, the higher the statistical power of analysis for detecting even subtle differences in methylation between samples [33]. ChIP data are represented as the mean ± SD of 6 different treatments (n=6) and analyzed by two-tailed paired t-test with significance level P < 0.05 as above.…”
Section: Methodsmentioning
confidence: 99%
“…All the samples were pooled, purified and then sequenced using the 600 cycle v3 kits. An average of about 10,000 reads were obtained per sample, hence increasing the statistical power of analysis 40 as compared to the Sanger sequencing. The data from Bismark’s text file outputs were compiled together and the percent DNA methylation changes were displayed using heat-maps ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…This is likely because each cell has two alleles of each gene, and alleles of minor cell types have stochastically lower chances of being sequenced than major cell types when only a few tens of clones are selected for bisulfite sequencing analysis. In addition, a previous study demonstrated the difficulty in detecting relatively subtle differences in methylation levels for small numbers of clones [ 26 ]. To our knowledge, the present study is the first to focus on hypomethylation of each sequenced read (transcriptionally active allele) obtained by ultra-deep bisulfite sequencing of cell type-restricted genes, which can reliably detect hypomethylation of minor cell types by sequencing hundreds or thousands of bisulfite PCR fragments of cell type-restricted genes.…”
Section: Discussionmentioning
confidence: 99%